2016
DOI: 10.4103/0975-7406.171700
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the ocean for new drug developments: Marine pharmacology

Abstract: Disease ailments are changing the patterns, and the new diseases are emerging due to changing environments. The enormous growth of world population has overburdened the existing resources for the drugs. And hence, the drug manufacturers are always on the lookout for new resources to develop effective and safe drugs for the increasing demands of the world population. Seventy-five percentage of earth's surface is covered by water but research into the pharmacology of marine organisms is limited, and most of it s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
219
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 347 publications
(227 citation statements)
references
References 35 publications
1
219
0
7
Order By: Relevance
“…Inhibitory effects on the enzyme PTP1B have been reported for a polybromodiphenyl ether from the Indonesian marine sponge Lamellodysidea herbacea [75] and for the terpene Dysidine, from the sponge Dysidea sp. [23,76], that has recently entered pre-clinical trials for the treatment of type-2 diabetes [23]. Dysidine was found for the first time in a sponge at Lahdu (Santo) in Vanuatu in June 1996, identified as sponge Dysidea sp.…”
Section: Marine Macroorganisms With Anti-diabetes Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibitory effects on the enzyme PTP1B have been reported for a polybromodiphenyl ether from the Indonesian marine sponge Lamellodysidea herbacea [75] and for the terpene Dysidine, from the sponge Dysidea sp. [23,76], that has recently entered pre-clinical trials for the treatment of type-2 diabetes [23]. Dysidine was found for the first time in a sponge at Lahdu (Santo) in Vanuatu in June 1996, identified as sponge Dysidea sp.…”
Section: Marine Macroorganisms With Anti-diabetes Propertiesmentioning
confidence: 99%
“…In addition, the cytotoxicity test against Hela cell line (from Homo sapiens cervix) showed no toxicity for this compound [78]. Malve et al [23] reported this compound in preclinical studies and to our knowledge it is not yet in clinical trials.…”
Section: Marine Macroorganisms With Anti-diabetes Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine-derived drugs like homotaurine, bryostatin, cytarabine, trabectedin, eribulin, and ziconotide have shown beneficial effects in neurodegenerative diseases, that included AD [116,117] . Some of these drugs have entered clinical studies [116,117] .…”
Section: Role Of Traditional Medicinementioning
confidence: 99%
“…Some of these drugs have entered clinical studies [116,117] . Currently clinical trials evaluating the role of Bry-1 (bryostatin) and homotaurine in management of AD have been in progress [116,117] .…”
Section: Role Of Traditional Medicinementioning
confidence: 99%